2012
DOI: 10.1063/1.3696164
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength study of the first γ-ray emitting LMXB XSS J12270-4859

Abstract: A multiwavelength strategy for identifying celestial γ-ray sources AIP Conf.Abstract. Fermi is discovering many new γ-ray sources, and 1FGL J1227.9-4852 is one of them. Recent studies suggest that this source is associated with the X-ray source XSS J12270-4859 (hereafter J12270), of which nature is poorly understood. In this paper, we show results of our Suzaku and RXTE X-ray observations which are partly simultaneous with near-infrared (NIR) observations using InfraRed Survey Facility (IRSF). We found that J1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…The nIR IRSF photometry gives the source at: J=15.39(8), H=15.08(8) and Ks=14.9(2) consistent with the measures in 2009 reported by dM10 and by Saitou et al (2011). The light curves, though with lower temporal resolution, display the same variability seen in the U band (Fig.…”
Section: The Variability During the Persistent Statesupporting
confidence: 83%
See 1 more Smart Citation
“…The nIR IRSF photometry gives the source at: J=15.39(8), H=15.08(8) and Ks=14.9(2) consistent with the measures in 2009 reported by dM10 and by Saitou et al (2011). The light curves, though with lower temporal resolution, display the same variability seen in the U band (Fig.…”
Section: The Variability During the Persistent Statesupporting
confidence: 83%
“…Surprisingly we also found XSS J1227 to be positionally coincident with the high energy gamma-ray Fermi -LAT source 1FGL J1227.9-4852/2FGL J1227.7-4853 emitting up to 10 GeV (dM10). Multi-wavelength follow-up observations, performed by Hill et al (2011), Saitou et al (2011) andde Martino et al (2013a, henceforth dM13), showed persistent X-ray and high energy gamma-ray emissions over an interval of at least ∼ 7 yr, making it an unique case among known galactic binaries with comparable X-ray and gammaray luminosities. The detection of a radio (Hill et al 2011) and gamma-ray (dM10) counterpart, together with a putative 4.5 h orbital period (dM10), led to the suggestion that XSS J1227 could host a MSP (Hill et al 2011), sharing similar properties with PSR J1023+0038 (Wang et al 2009;Tam et al 2010;Archibald et al 2010).…”
Section: Introductionmentioning
confidence: 99%